Feasibility and effectiveness of interpersonal psychotherapy interventions in a collaborative stepped care model between primary care and mental health services. (13th April 2021) - Mongelli, F.; Martino, F.; Berardi, D.; Colombini, N.; Ferrari, S.; Menchetti, M.
Abstract : Introduction: The NICE guidelines recommend for mild major depression a range of low-intensity psychosocial intervention of proven effectiveness, as Interpersonal Counselling, and a stepped-care approach. Objectives: To assess feasibility and effectiveness of Interpersonal Psychotherapy interventions for the treatment of depression in a consolidated Collaborative Stepped Care Model between primary care and mental health specialists. Methods: 103 patients were referred by their PCPs to the Consultation-Liaison Service of Bologna and Modena. Of them, 78 were included in the study and administered self-report instruments and interview, including screening depression, anxiety and daily functioning. Patients were asked to choose one of the available treatment: 1) Interpersonal Counseling (IPC) 6-8 weekly meetings for 30 minutes; 2) IPC for Depression in Primary Care 3 sessions of 50 minutes; 3) a guided self-help intervention. Follow-up were planned at 1, 3 and 6 months. Both patients and PCPs provided a feedback about intervention's satisfactions. Results: At the baseline, 39.4% of the patients presented a minor depression/major depression mild and the large majority (75.0%) of them chose IPC, while none of them chose the guided self-help intervention. At follow ups the mean PHQ-9 significantly decreased compared to the baseline (p<0.001); daily functioning increased (WSAS: p<0.001) and anxiety traits improved (STAI: p<0.001). Patient's general satisfaction with the service received was high (GSQ: 85.9±15.0) as well as PCPs, 62.7% of them expressed high satisfaction for the intervention. Conclusions: The study emphasised that IPC is an effective and feasible treatment very well suited to the primary care setting for an optimal management of depression.